Oncolytic Adenovirus Coding for a Variant Interleukin 2 (vIL-2) Cytokine Re-Programs the Tumor Microenvironment and Confers Enhanced Tumor Control - Quixabeira, Dafne C. A.; Zafar, Sadia; Santos, Joao M.; Cervera-Carrascon, Victor; Havunen, Riikka; Kudling, Tatiana V.; Basnet, Saru; Anttila, Marjukka; Kanerva, Anna; Hemminki, Akseli (Frontiers in Immunology, 2021)
The notion of developing variants of the classic interleukin 2 (IL-2) cytokine has emerged from the limitations observed with the systemic use of human IL-2 in the clinic: severe adverse events accompanied by low therapeutic response rate in treated patients. Modifications made in the IL-2 receptor-binding structure leads to preferential binding of IL-2 variant cytokine to receptors on effector anti-tumor lymphocytes over T regulatory (TReg) cells. Because of their inherent immunogenicity, oncolytic adenoviruses are useful for expression of immunomodulatory molecules in tumors, for induction of a pro-inflammatory state in the tumor microenvironment. In the present study, we constructed an adenovirus coding for an IL-2 variant (vIL-2) protein, Ad5/3-E2F-d24-vIL2. Functionality of the new virus was tested in vitro, and anti-tumor efficacy and mechanism of action studies were performed in immunocompetent hamsters bearing pancreatic tumors. Ad5/3-E2F-d24-vIL2 treatment elicited efficient anti-tumor response, with 62.5% monotherapy complete response. Moreover, it promoted substantial repression of genes associated with myeloid cells mediated immunosuppression (CD11b, ARG1, CD206). This was seen in conjunction with upregulation of genes associated with tumor-infiltrating lymphocyte (TIL) cytotoxicity (CD3G, SAP, PRF1, GZMM and GZMK). In summary, Ad5/3-E2F-d24-vIL2 demonstrates therapeutic potential by counteracting immunosuppression and in efficiently coordinating lymphocytes mediated anti-tumor response in immunosuppressive tumors. Thus, Ad5/3-E2F-d24-vIL2 is a promising candidate for translation into clinical trials in human immunosuppressive solid tumors.